The determinant of insurance demand in Malaysia - Hamidon, Nadiah (2019)
The aim of this paper is to examine the factors that influencing the insurance demand in Malaysia. The demand of insurance (INS) is choose as the dependent variable in this study, There are three independent variables to be used which are Interest rate(INT), Inflation(INF) and Gross National Expenditure (GNE). Annual data is gathered over the period 1980 to 2018. The data is gathered from World Data Indicators (WDI) . The statistical test applied in this study which is, Descriptive Analysis, multiple linear regressions, Augmented Dickey Fully (ADF) Unit Root Test, Philip-Perron (PP) Unit Root Test, Normality Test, and multicollinearity test. Interactive software package E-view would be used for testing and analyzing the data collected. Moreover, the expected finding is interest rate (INT) has significant relationship with the demand of insurance. On the other hand, inflation (INF) and gross national expenditure (GNE) has insignificant relationship with the demand of insurance.